Bloomfield, Mo., Rev. Ordinances ch. 12, art. 3, § 50 (1898) - (:unkn) unknown (My University, 1898)
Ch. 12, Art. 3, § 50: arrying Deadly Weapons, Discharging Fire-Arms, etc: If any person shall carry concealed upon or about his person any deadly or dangerous weapon, or shall go into any church or place, within this city, where people are assembled for religious worship, or into any school room or place where people are assembled in this city, for educational, or social purposes, or to any election precinct, in this city on any election day, or into any court room during the sitting of court, or into any other public assemblage of persons, in this city, met for any lawful purpose other than for malitia [sic] drill, or meeting called under the militia laws of this State, having upon or about his person any kind of firearms, bowieknife [sic], dirk, dagger, slung shot or other deadly weapon, or shall, in the presence of one or more persons, exhibit any such weapon in a rude, angry or threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated, or under the influence of intoxicating drinks, or shall, directly or indirectly, sell or deliver, loan or barter to any minor any such weapon, without the consent of the parent or guardian of such minor, he shall, upon conviction, be punished by a fine of not less than fifty nor more than two hundred dollars, or by imprisment [sic] in the city calaboose, or city jail not less than five days nor more than six months, or by both such fine and imprisonment.
Keywords: BRANDISHING; CARRY - CONCEALED; TRANSFER - MINORS